A refined method to study gene dosage changes in-vitro using CRISPR/Cas9 - Raposo, T.P.; Ebili, Henry; Ilyas, Mohammad (BMJ Publishing Group Ltd, 2017)
Aims: Gene dosage can have a major impact on cell biology although, hitherto, is has been difficult to study using in-vitro models. We sought to refine and accelerate the development of “gene dosage” models through using CRISPR/Cas9 (a gene-editing technology) for sequential knockout of gene alleles. Methods: Our method involved (i) using Cas9 nuclease mRNA rather than expression plasmids, (ii) using a fluorescently labelled FAM-6 tracr complexed with guide RNA and (iii) using High Resolution Melting (HRM) analysis to screen for mutations. HCT116 cells, wild-type for TP53, were transfected with different molarities of FAM-6 tracr labelled and guide RNA targeting different exons of TP53 and selected by Fluorescence Associated Cell Sorting (FACS). Single-cell colonies were then isolated, expanded and tested for mutation in the targeted region by PCR/HRM. Results: Out of 32 clones tested, 12 have shown aberrant melting by HRM, giving a targetting efficiency of 37.5%. One clone was sequenced and a heterozygous mutation found - in this case comprising a single base deletion in exon 3. mRNA sequencing confirmed the mutation was expressed and western blotting for p53 showed the presence of both wild type and truncated protein bands. Changes in expression of MDM-2 isoforms suggested a functional effect of the induced TP53 mutation. Conclusions: We have developed an in-vitro model to study TP53 gene dosage effects. The protocol is efficient and applicable to any gene. Importantly, we have used Cas9 mRNA and labelled tracr/guideRNA to isolate likely-mutated cells and HRM for rapid mutation detection.